(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
This study evaluated the toxicity of Leachate from Ojota, Lagos dumpsite on the kidney and liver of male Wistar rats. Forty-five male albino rats weighing 180 Â±5.5 grams were randomly divided into five groups (n=9). Group A rats drank distilled water throughout the experimental period while rats in group B, C, D and E were exposed to 25%, 50%, 75% and 100% leachate via drinking water for 45 days respectively. Daily intake of leachate was measured for each group. On the last day, the animals were fasted 8 hours overnight and blood samples were collected for liver and kidney function tests. Our finding revealed that rats exposed to 25%, 50% and 75% drank more of the leachate. There were marked increase (P<0.05) in the activities of aspartate aminotransferase (AST) and alkaline phosphatase (ALP) in rats exposed to different concentrations of the leachate. Rats exposed to 75% and 100% leachate showed significant increase (P<0.05) in serum Alanine aminotransferase (ALT) activity, Î³-glutamyltransferase (GGT) activity was higher in other groups compared to control, while rats exposed to 25% and 50% leachate had increase in the serum direct bilirubin concentration (P<0.05). Creatinine level was markedly high in rats exposed to 100% leachate while the rats that were exposed to 50% and 100% leachate had elevated urea level. Conclusively, leakage of leachate into water bodies especially ground water and its exposure through drinking may pose a high risk on liver and kidney function.